Uncertainty analysis along the ecological quality status of water bodies: The response of the Posidonia oceanica multivariate index (POMI) in three Mediterranean regions - Mascaró, O.; Bennett, Scott; Marbà, N.; Nikolic, V.; Romero, J.; Duarte, C.; Alcoverro, T. (Elsevier, 2012)
Uncertainty analyses allow the identification and quantification of the factors that contribute to the potential misclassification of the ecological status of water bodies, helping to improve the sampling design used in monitoring. Here we used a Posidonia oceanica multivariate index (POMI) bio-monitoring dataset covering a total of 81 sites distributed throughout 28 water bodies from the coast of Catalonia, Balearic Islands and Croatia to determine the levels of uncertainty associated with each region and how they change according to the quality status of water bodies. Overall, variability among sites (meadows) within water bodies was the factor that generated the greatest risk of misclassification among the three regions, within which the Balearic Islands had the lowest uncertainty, followed by Croatia and Catalonia. When water bodies classified in good/high quality were separated from those in moderate/poor status classes, we found that the latter displayed higher levels of uncertainty than the former. © 2012 Elsevier Ltd.